Analysis of Learning Styles among Grade VII Students in Learning English at SMP Negeri 1 Tapa - Jihan D. Pasisingi; Helena Badu; Fahria Malabar (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the types of learning styles used by Grade VII students of SMP Negeri 1 Tapa in learning English and to determine which learning style is most dominantly used. The study applies the VAK (Visual, Auditory, Kinesthetic) learning style model as the theoretical framework. A quantitative descriptive method. The instrument used in this research was a structured questionnaire consisting of 30 statements, with each 10 items representing one learning style category. The results showed that all three learning styles were present among the students. The visual learning style was identified as the most dominant, followed by auditory and kinesthetic. Students with visual preference tended to understand English better when exposed to images, texts, and visual aids. These findings suggest that English teaching should consider students' learning preferences to support more effective and differentiated instruction. This research highlights the importance of understanding student learning styles to improve engagement and learning outcomes.